Variability of protease activity and growth rate in isolates of Macrophomina phaseolina from various hosts - Hobson, Sam; Waite, Natalie; Little, Christopher R (My University, 2022)
Macrophomina phaseolina is a necrotrophic fungal pathogen that causes charcoal rot, among other diseases, on over 500 plant hosts and economically important crops in Kansas such as soybean and sorghum. Because it thrives in hot, dry environments, global climate change threatens to make this pathogen increasingly difficult to manage. M. phaseolina has a relatively low number of genes encoding proteases, protein-lysing enzymes commonly employed by plant pathogens. Further, their effect on virulence has been understudied. Three-hundred thirteen isolates of M. phaseolina from a variety of hosts were cultured on potato dextrose agar (PDA) plates to measure growth rate over one week, then were cultured on casein agar (CNA) to assess proteolytic activity over one week. Clearing zones that formed around the colonies on CNA represent areas where protein had been lysed, thus distinguishing isolates by their proteolytic activity. We hypothesize that different isolates will demonstrate varying levels of protease activity. This would shed light on the role that proteases play as a virulence factor for M. phaseolina and how this role may shift depending on the host and genetic identity of the isolate. Better understanding of M. phaseolina virulence mechanisms is vital to manage this pathogen, especially as climate change exacerbates the environmental conditions that promote charcoal rot.
Keywords: plant pathology; Macrophomina phaseolina; charcoal rot; protease activity; virulence mechanism; USDA NIFA 2019-67032-29071